Geometric Analysis of Luciobarbus barbulus (Heckel 1847) Otoliths With Body Shape - Funda Aksunger Karaavci; Yasin Demiraslan; Muhammed Yasar Dortbudak; Ismail Demircioglu (Veterinary Medicine and Science, 2025)
ABSTRACT Background The Cyprinidae family is one of the most varied families in terms of number of species, representing approximately 1500 species in the world. Luciobarbus barbulus (Heckel 1847) is a little‐known species, but it is widespread in the Tigris and Euphrates rivers. The aim of the study was to analyse the body shape and otoliths of L. barbulus species by geometric morphometry to better distinguish the population structure of the fish. Materials and Method In this study, 34 barbulus and their otoliths were used. General Procrustes Analysis (superimposition), principal component analysis (PCA), multivariate regression analysis, Partial Least Squares and discriminant function analysis were applied. Results Multivariate regression analysis revealed a 9.1174% effect of size on otolith shape. PCA calculated 33 components for the otoliths in the study, and the first 3 components explained 64.027% of the total shape variation. The Partial Least Squares (PLS) analysis revealed that there is no significant correlation between otolith and fish shape. As a result of the discriminant function analysis, 33.33% (4:12) of female otoliths and 36.36% (8:22) of male otoliths were correctly grouped. Conclusion This study revealed that otolith shape analysis is an effective tool for deciphering the population structure of small pelagic species. It was also found that there is no difference between otolith and fish shape as otolith biomineralization is influenced by many factors.